Genetic diversity of tropical early-maturing maize inbreds and their performance in hybrid combinations under drought and optimum growing conditions - Oyekunle, M.; Badu-Apraku, Baffour; Hearne, S.; Franco, J. (Elsevier, 2015)
Hybrid development is enhanced by the assessment and understanding of genetic diversity and distance within inbreds. One hundred and fifty hybrids derived from 30 early-maturing inbreds plus six checks were evaluated at three locations in Nigeria for 2 years to assess their performance under drought and well-watered conditions. In addition, twenty three microsatellite markers were employed to assess genetic diversity of selected 42 inbreds. Significant differences were observed among inbreds and hybrids for most traits under both research conditions. A total of 130 alleles were detected ranging from two for nc133 to nine for phi299852 with an average of 5.7 alleles per locus. Polymorphic information content ranged from 0.17 for phi308707 to 0.77 for phi084 with an average of 0.54. Thirty-one unique alleles were detected in 21 inbreds. Microsatellite markers classified the inbred lines into five groups. Genetic distance estimates among pairs of inbreds ranged from 0.42 (TZEI 26 vs TZEI 108) to 0.85 (TZEI 24 vs TZEI 4) with an average of 0.67. Correlation between microsatellite-based GD estimates of the parental lines and their F1 hybrids were not significant for grain yield and other traits under drought and well-watered conditions. However, significant correlations existed between F1 hybrid grain yield and heterosis under drought and well-watered conditions. TZEI 31 × TZEI 18 was identified as the highest-yielding and stable hybrid across environments and should be promoted for adoption by farmers in West and Central Africa.